Serum protein profiling in patients with inflammatory bowel diseases using selective solid-phase bulk extraction, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and chemometric data analysis - Nanni, Paolo; Parisi, Daniela; Roda, Giulia; Casale, Monica; Belluzzi, Andrea; Roda, Enrico; Mayer, Lloyd; Roda, Aldo (Rapid communications in mass spectrometry, 2007)
The identification of new biomarkers or a disease‐related protein fingerprint for inflammatory bowel diseases (IBDs) represents a major task in the diagnosis, prognosis and pharmacological therapy. To address these issues, a simple and rapid analytical proteomic method for serum protein profiling based on selective beads‐based solid‐phase bulk extraction, matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) and chemometric data analysis was developed. Serum proteins from healthy subjects (22) and patients with Crohn's disease (15) and ulcerative colitis (26) were selectively extracted according to reversed‐phase (C18), strong anion‐exchange (SAX) and metal ion affinity (IDA‐Cu(II)) principles. This approach allowed enrichment of serum proteins/peptides due to the high interaction surface between analytes and the solid phase and high recovery due to the elution step performed directly on the MALDI‐target plate. The MALDI‐TOF MS serum protein profiles were acquired and, after a data pre‐processing step, analyzed by linear discriminant analysis (LDA), a chemometric classification technique, in order to classify serum samples among healthy subjects and patients with inflammatory bowel diseases (IBDs). Since the high number of variables in the MALDI spectra (more than 16000 m/z values) prevents the use of LDA, the variables were reduced to 10–20 by features selection, thus allowing the evaluation of a pattern of m/z values with high discriminant power. Serum protein profiles obtained by reversed‐phase extraction and the selection of 20 m/z values gave the best overall prediction ability (96.9%). The recognition of these m/z values may allow the identification of protein biomarkers involved in IBDs. Copyright © 2007 John Wiley & Sons, Ltd.